IMPORTANCE OF THE UNIVERSAL SERVICE IN THE CONTEXT OF THE DEBATE OVER THE RIGHT TO ACCESS TO THE INTERNET - Przemysław PALIWODA; Bartłomiej Bąk (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The paper presents universal service regulation seen as an expression of positive aspect of the right to the Internet access. It describes how the relevant regulation developed and discusses its implementation in a chosen national legal systems and talks about the role it is being assigned to play in the future as a part of potential complex system of the Internet access regulation.